Improved Explicit Integration Algorithms for Structural Dynamic Analysis with Unconditional Stability and Controllable Numerical Dissipation - Kolay, Chinmoy; Ricles, James M. (Journal of earthquake engineering : JEE, 2019)
A computationally efficient one-parameter family of explicit (i.e., non iterative for nonlinear systems) direct integration algorithms featuring second-order accuracy, unconditional stability for linear systems, and controllable numerical dissipation is developed for solving inertial problems. Unconditional stability is attained within an explicit formulation using the concept of model-based algorithms in which the algorithmic parameters are functions of the model matrices. The proposed method improves the overshoot and nonlinear stability characteristics of the KR- method, an existing explicit-model-based algorithm. Numerical characteristics of the proposed method are compared with those of the KR- method and further demonstrated through representative numerical examples.